A New Insight on the Symbiotic Association between the Fan Mussel Pinna Rudis and the Shrimp Pontonia Pinnophylax in the Azores (NE Atlantic) - Joao P Barreiros; Ricardo JS Pacheco; Sílvia C Gonçalves (Global Journal of Zoology - Peertechz Publications, 2016)
Bivalves Pinnidae are typical hosts of Pontoniinae shrimps. Several species of this family were documented to harbor these decapods inside their shells, especially shrimps from the genus Pontonia [1,2]. The present record is the first ecological study on the symbiotic association between the fan mussel Pinna rudis Linnaeus, 1758 and the shrimp Pontonia pinnophylax (Otto, 1821) in European Atlantic shallow waters - Azores (Portugal). During a series of exploratory dives to a maximum depth of 20m, along 13 sites on the south coast of Terceira Island, a total of 28 bivalves were checked for the presence of P. pinnophylax between August and October of 2004.